How master Mou removes our doubts : a reader-response study and translation of the Mou-tzu Li-huo lun - Keenan, John P., 1940- (SUNY series in Buddhist studies., 1994)
This is the first English translation of the earliest Chinese Buddhist text, but it is more than a translation. Keenan shows that Mou-tzu's "Treatise on Alleviating Doubt" is a Buddhist hermeneutic on the Chinese classics. Using a reader-response method of examining the text, Keenan shows how the rhetoric convinces readers that one can remain culturally Chinese yet be a Buddhist. The Introduction explains the reader-response methodology, develops the movement of the dialogue in terms of this method, and clarifies the rhetorical impact of Master Mou's argument. This is followed by the thirty-seven articles of the text. Each article is first translated into English, then the contextual images and ideas are unpacked for each, and finally each article is subjected to a reader-response critique that shows what the argument accomplishes in each of its progressive steps